OPTIMALISASI LAYANAN PASIEN UMUM DAN KUSTA DI RSUD KELET - Tri Risandewi (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
Data from the Indonesian Ministry of Health as of April 2019 shows that Central Java Province is one of the provinces that has a number of new cases of leprosy as much as 1,445 or 8.49 percent of the total number of cases in Indonesia. Kelet Hospital as one of the referral hospitals for leprosy patients needs to improve the quality of service for leprosy patients even though it has switched to a hospital. Therefore, it is necessary to conduct research on the consequences of the spread of leprosy on leprosy patient services in Central Java Province and how the quality of service to leprosy patients and the general public. and how the strategy of Kelet Hospital in improving the quality of patient care. The research method used is descriptive qualitative, with data collection methods through document review, observation, FGD and in-depth interviews. The location of this research is in Kelet Hospital, Jepara Regencyand several regency/ cities with detected cases of leprosy (Blora, Brebes, City of Pekalongan, etc.) The results of the study show that the impact of the spread of leprosy on leprosy patient services in Central Java currently causes leprosy services in health facilities to be not optimal due to the referral system levels, access to referral hospitals is too far away, management and care for leprosy patients in health facilities is still inadequate and there is a negative stigma from the community. The change in the status of the special hospital for leprosy to become RSUD Kelet for leprosy services does not have a negative impact, but instead is able to become a supporting system for leprosy patient services and is able to have a positive impact on increasing the income of Kelet Hospital. The future development strategy is to develop Kelet Hospital as a center of excellence, a cancer research center hospital and a research-based leprosy hospital and integrate health, environment and tourism with the development of the area around RSUD Kelet Jepara.